Whale watching disrupts feeding activities of minke whales on a feeding ground - F Christiansen; M Rasmussen; D Lusseau (2013)
Human disturbances of wildlife, such as tourism, can alter the activities of targeted individuals. Repeated behavioural disruptions can have long-term consequences for individual vital rates (survival and reproduction). To manage these sub-lethal impacts, we need to understand how activity disruptions can influence bioenergetics and ultimately individual vital rates. Empirical studies of the mechanistic links between whale-watching boat exposure and behavioural variation and vital rates are currently lacking for baleen whales (mysticetes). We compared minke whale Balaenoptera acutorostrata behaviour on a feeding ground in the presence and absence of whale-watching boats. Effects on activity states were inferred from changes in movement metric data as well as the occurrence of surface feeding events. Linear mixed effects models and generalised estimation equations were used to investigate the effect of whale-watching boat interactions. Measurement errors were quantified, and their effects on model parameter estimates were investigated using resampling methods. Minke whales responded to whale-watching boats by performing shorter dives and increased sinuous movement. A reduction in the probability of observing longer inter-breath intervals during sinuous movement showed that whale-watching boat interactions reduced foraging activity. Further, the probability of observing surface feeding events also decreased during interactions with whale-watching boats. This indicates that whalewatching boats disrupted the feeding activities of minke whales. Since minke whales are capital breeders, a decrease in feeding success on the feeding grounds due to whale-watching boats could lead to a decrease in energy available for foetus development and nursing on the breeding grounds. Such impact could therefore alter the calving success of this species.